The Western Equine Encephalitis Lyophilized, Inactivated Vaccine: An Update on Safety and Immunogenicity - Keshtkar-Jahromi, Maryam; Reisler, Ronald B.; Haller, Jeannine M.; Clizbe, Denise P.; Rivard, Robert G.; Cardile, Anthony P.; Pierson, Benjamin C.; Norris, Sarah; Saunders, David; Pittman, Phillip R. (Frontiers in Immunology, 2020)
Background: Western Equine Encephalitis (WEE) is a naturally acquired infection and potentially devastating bioweapon, with no specific human countermeasures. An experimental inactivated Western Equine Encephalitis Vaccine (WEEV; WEE TSI-GSD 210) has been used under an IND (investigational New Drug) protocol at the United States Army Medical Research Institute of Infectious Diseases (USAMRIID) since 1976. Methods: Over 24 years from 1987-2011, 876 subjects received 3 primary vaccine doses under 3 studies with 1,537 booster doses administered (FY87-8, Phase 2, laboratory workers, vaccine lots 1-81-1, 1-81-2 and 2-1-91; FY99-12, Phase 2 laboratory workers, lot 2-1-91; and FY09-02, Phase 1 healthy volunteer, lot 3-1-92). Post-vaccination safety and immunogenicity (plaque reduction neutralization test 80% (PRNT80) >1:40) were analyzed. Results: Overall PRNT80 response to the primary series in FY87-8 was 42% (326/770), but dropped to 16% (14/87) in FY99-12, prompting study FY09-02 which achieved 89% (17/19). The first booster response rate was 68% (814/1194) in FY87-8, 53% (171/324) in FY99-12, and 100% (10/10) in FY09-02. The majority of definitely related adverse reactions (AEs) were mild and local with no definitely related serious AEs. No laboratory acquired WEE infection was documented during this period despite 4 reported exposures in vaccinated subjects. Conclusion: The TSI-GSD 210 WEE vaccine was immunogenic, safe and well tolerated. Use of this vaccine could be considered in an emergency setting. Despite decades of safe and effective use under IND, full licensure is not planned due to manufacturing constraints, and a strategic decision to develop alternatives. Phase 1 FY09-02 Clinical Trials Registration. NCT01159561